Oxidative disproportionation of MoS2/GO to MoS2/MoO3-x/RGO : integrated and plasmonic 2D-multifunctional nanocomposites for solar hydrogen generation from near-infrared and visible regions - Patra, Kshirodra Kumar; Ghosalya, Manoj Kumar; Bajpai, Himanshu; Raj, Sreeya; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2019)
Two dimensional (2D) semiconductor materials have been recently demonstrated to be effective plasmonic materials and alternatives to costly noble metals. However, tuning the plasmon resonance of 2D semiconductors and integrating with another material or semiconductor for various applications, such as solar light harvesting, remains a challenge. Herein, we designed a simple and attractive method, which facilitates the diffusion of oxygen from the graphene oxide (GO) layers of the MoS2/GO (MG) composite to oxidize the MoS2 layers significantly due to thermal treatment under inert atmosphere. This is the key step in the formation of MoS2/MoO3-x/RGO (MMR) (x = 0, 0.5, and 1, and all stoichiometries co-exist), due to disproportionation of MoS2/GO, with bulk heterojunctions among the components. The observed behavior is attributed to the oxidation of Mo4+ cations (of MoS2) to higher oxidation states in MMR (Mo(5+ )and Mo6+ of MoO3-x), which also alters the valence-band electronic structure and work function of the resulting composite. The 2D MoO3-x layers with a large amount of Mo5+ oxidation states enables facile charge carrier generation due to plasmonic effect, whereas MoS2 provides active sites for catalysis. The solar H-2 generation was demonstrated in the visible and near-infrared region by combining both the plasmonic and catalytic effects in one composite. These results demonstrate the important role of RGO to provide energy-level alignment, charge carrier diffusion, and help to generate plasmonic effect in the composite.

Can half-a-monolayer of pt simulate activity like that of bulk pt? solar hydrogen activity demonstration with quasi-artificial leaf device - Bajpai, Himanshu; Patra, Kshirodra Kumar; Ranjan, Ravi; Nalajala, Naresh; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2020)
Pt is the best cocatalyst for hydrogen production. It is also well-known that the surface atomic layer is critical for catalysis. To minimize the Pt content as cocatalyst, herein we report on half-a-monolayer of Pt (0.5 theta(Pt)) decorated on earth-abundant Ni-Cu cocatalyst, which is integrated with a quasiartificial leaf (QuAL) device (TiO2/ZnS/CdS) and demonstrated for efficient solar hydrogen production. For the QuAL, TiO2 is sensitized with ZnS and CdS quantum dots by the SILAR method. The 0.5 theta(Pt)-decorated Ni-Cu shows an onset potential of 0.05 V vs reversible hydrogen electrode for the hydrogen evolution reaction, which is almost similar to that of commercial Pt/C. Photoactivity of the present QuAL device with either bulk Pt or 0.5 theta(Pt)-coated Ni-Cu cocatalyst is, surprisingly, equal. Our findings underscore that a fraction of a monolayer of Pt can enhance the activity of the cocatalyst, and it is worth exploring further for the high activity associated with atomic Pt and other noble metals.
Keywords: artificial leaf; nickel-copper; Photocatalysis; platinum; Solar hydrogen

Sulfur functionalization via epoxide ring opening on a reduced graphene oxide surface to form metal (II) Organo-bis-[1,2]-oxathiin - Kumar, Praveen; Bajpai, Himanshu; Gopinath, Chinnakonda S.; Luwang, Meitram Niraj (Inorganic Chemistry, 2022)
The epoxide ring-opening reaction in graphene oxide (GO) by nucleophiles is a very fascinating and advanced methodology to develop novel functional material. Herewith, we report an advanced strategy for opening the epoxide ring on the rGO surface via easily an available nucleophile (Na2S), which is further functionalized with O atom to obtain four-membered rings (FMRs). The Cd coordination with the S atom puts extra stress on the FMR leading to the C-C bond cleavage of the four-membered heteroatomic rings on the rGO surface. This strategic approach leads to the fabrication of an innovative metal organo-bis-[1,2]-oxathiin (MOBOT) chemical moiety (M = Cd, Zn). The MOBOT compound further shows enhanced H-2 generation activity and hence is promising as a potential photocatalyst for solar hydrogen generation. This compound might also be a potential candidate for optoelectronic applications.

Baby step in assembling and integrating the components of an artificial photosynthesis device with forced heterojunctions towards improved efficiency - Salgaonkar, Kranti N.; Bajpai, Himanshu; Mhamane, Nitin B.; Nalajala, Naresh; Chauhan, Inderjeet; Thakkar, Kavita; Joshi, Kavita; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2023)
How to achieve unassisted, economical, scalable, and sustainable artificial photosynthesis for liquid fuels/products with improved solar-to-fuel efficiency (STFE) to address a carbon-neutral economy remains a big question. To a large degree, the extent of charge separation at heterojunction interfaces and charge utilization determine the STFE. Towards this, BiVO3 is assembled from ionic-precursors into TiO2 pores, and integrated structurally and electronically with TiO2 on calcination as BiVO4 quantum dots (BVQDs). BVQDs in TiO2 (BVT) pores lead to an all-inorganic system with a sub-quadrillion number of heterojunctions in a 1 cm(2) device (contains similar to 25 mu g of BiVO4 (similar to 2.5 wt%) in the nanopores of similar to 975 mu g of TiO2 (similar to 97.5 wt%)) and facilitate artificial photosynthesis. We demonstrate 31-38% STFE with a photon to chemical conversion turn over frequency (ToF(P2C)) of 2.73 s(-1) with a 1 cm(2) wireless BiVO4-TiO2 artificial leaf (BVT-AL) device for HCHO and CH3OH. The sequential nature of CO2 reduction to HCHO and then to CH3OH is evident from the reaction results. (CO2)-C-13 isotopic labeling experiments confirm that the input CO2 is the source for product formation. A large increase in the photocurrent density and incident photon-to-current efficiency (IPCE) of BVT, over 100% for the BiVO4 photoanode in visible light, demonstrates and supports efficient visible light absorption, charge separation and migration to the redox sites. A device has been demonstrated to show sustainable activity in direct sunlight, and addresses scalability from 1 to 9 cm(2). Assuming no change (50% decrease) in the STFE, a 6.74 m(2) device is expected to convert 1 (0.5) kg h(-1) CO2 into C1-oxygenates in sunlight. DFT calculations carried out with anatase TiO2 (101) and BiVO4 (121) interfaces support many of the experimental findings, including electron flow from the latter to the former, and interaction of the oxygen of TiO2 with BiVO4 and vice versa at the interface towards forced heterojunctions.

Cadmium (II) Organo Tetrakis-[1,2]-Oxathiin (CdOTOT): a 3D sandwiched frameworks with efficient hydrogen production - Kumar, Praveen; Bajpai, Himanshu; Luwang, Meitram Niraj (Journal of Catalysis, 2023)
For over a decade, the structure, reactivity, and mechanism of graphene based photocatalysts have been of great interest for hydrogen (H2) generation. Several studies have been done on the edge side groups (ESGs) of graphene oxide (GO), but the basal plane groups (BPGs)-epoxide and hydroxide have acquired far less attention. This is because the GO layers are strongly held with van der waals forces as well as H-bonding which prevents the foreign body from entering inside the layers. To overcome these problems, this study presents the successful synthesis and application of four coordinated sandwiched (FCS) Cadmium (II) Organo Tetrakis-[1,2]-Oxathiin (CdOTOT) in rGO-CdS composite (A 3D sandwiched frame-work). Additionally, experimental outcomes have been further supported using density functional theory (DFT), which suggest that CdOTOT is more stable than its precursors as well as thermodynamically favourable. The CdOTOT shows high H2 production activity -67.5 mmol/g or 13.5 mmol/g/h in presence of 1 % Pt cocatalyst and sacrificial reagents (Na2S/Na2SO3). It is around 33 times higher than pristine CdS, and stable up to around 15 hrs without adding any cocatalyst. This mesmerising outcome is over with reported various CdS-rGO based photocatalysts. The higher activity was further explained through the proposed mechanism and observed low electronic work function of CdOTOT. This innovative and extend-able (with other metals) approach provides a revolutionary impact on numerous cutting-edge research applications like photocatalysis, water splitting, solar cell, etc.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: 2]; 3D sandwiched frameworks; Basal Plane Groups (BPGs); Cadmium (II) Organo Tetrakis-[1; hydrogen production; Oxathiin (CdOTOT)

Nanostructured Co-doped BiVO4 for efficient and sustainable photoelectrochemical chlorine evolution from simulated sea-water - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Bajpai, Himanshu; Mhamane, Nitin B.; Salgaonkar, Kranti N.; Gopinath, Chinnakonda S. (Dalton Transactions, 2023)
The co-production of hydrogen and chlorine from sea-water splitting could be a potential, sustainable and attractive route by any method. However, challenges to overcome are many, and critically, the sustainability and operating potential of the electrocatalyst are important. In this work, we report on Co-doping in the BiVO4 (Co-BV) crystal lattice and employed the same as the photoanode; Co-BV exhibits a photocurrent of 190 mu A cm(-2) at 1.1 V vs. RHE (the reversible hydrogen electrode) in the acidic sodium chloride solution (pH 2.3) under one sun illumination. The best-performing photoanode, with 0.05 mol% of Co doping (0.05 Co-BV), selectively produced active chlorine with 92% faradaic efficiency at 1.1 V vs. RHE by successfully suppressing the kinetically sluggish oxygen evolution reaction (OER) and the stability of the catalyst was demonstrated for up to 20 h. This is the lowest operating potential reported for the chlorine evolution reaction (CER), thus far. The overpotential required for CER with 0.05 Co-BV is lower than that of OER, which leads to selective CER at 1.1 V (vs. RHE). Co-doping into the BiVO4 lattice decreases the charge transfer resistance and enhances the CER kinetics due to its structural and electronic integration with the BV lattice. We demonstrate that Co-doping also improves the lifetime of the charge carrier and enhances the current density of CER and sustainability of the catalyst.

Aqueous glycerol to glyceric acid and green hydrogen by visible-light-driven photocatalysis with Ni/Co(PO4)2-TiO2: parallel utilization of holes and electrons - Nivedhitha, Thazhath R.; Bajpai, Himanshu; Oommen, Jiffin Varghese; Abraham, Athira; Chauhan, Inderjeet; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2024)
Replacing the kinetically sluggish oxygen evolution reaction (OER) with the oxidation of an abundantly available organic molecule to value-added product(s) (VAPs) at low voltage along with the hydrogen evolution reaction (HER) is a big challenge in water splitting, either by electrolysis or sunlight-driven photocatalysis. Glycerol oxidation to a VAP is kinetically fast, compared to an OER, and offers hope to enhance sunlight-driven water splitting to hydrogen by the concurrent utilization of holes and electrons. Mixed bimetal phosphates of Co and Ni (CoxNiy(PO4)(2) (CoNiP)) with different Co:Ni ratios (10:0, 7:3, 5:5, 3:7, and 0:10) were integrated with TiO2 to generate final photocatalyst composites (x wt % CoNiP with TiO2) and employed for concurrent photocatalytic HER and glycerol oxidation. Irrespective of the weight ratios of CoNiP and TiO2, any TiO2-CoNiP composite showed better photocatalytic activity for the HER and glycerol oxidation compared to virgin TiO2. The highest HER as well as selectively generated glyceric acid yield was observed to be 54 and 67 mmol/g, respectively, after 25 h of reaction under 1 sun conditions with TiO2-CoNiP-5:5. An increase in catalytic activity can be attributed to the formation of p-n heterojunctions of the constituent component along with uniform distribution of CoNiP to effectively utilize the charge carriers for redox reactions. Highly selective oxidation of glycerol to glyceric acid (85%), along with other minor products, is also demonstrated, which offers further scope to use solar light to generate VAPs in a sustainable manner. A simple comparison of H-2 yield and all oxidized products together indicates the better utilization of holes for the latter, and hence, there is scope to increase HER and possibly the whole photocatalytic activity.
Keywords: biomass component; earth-abundantmaterial; energy conversion; organicvalorisation; water splitting

Design of Bi-functional mixed oxide electrodes for selective oxidative C-C cleavage of glycerol to formate and synchronized green hydrogen production - Saha, Arindam; Murugiah, Vasantharadevi; Ranjan, Ravi; Chauhan, Inderjeet; Patra, Kshirodra Kumar; Bajpai, Himanshu; Saha, Avisekh; Gopinath, Chinnakonda S. (Sustainable Energy & Fuels, 2024)
Alkaline water electrolysis is a mature method to produce green hydrogen; however, it suffers from significantly high cost as high overpotentials are required for the oxygen evolution reaction (OER). However, the OER could be avoided altogether by replacing it with kinetically favorable oxidation of abundantly available feedstock molecules at a significantly low potential to value-added product(s) together with green hydrogen generation. This is a potential method to address the high cost of green hydrogen production while converting waste to wealth. Herein, we report green, template-free hydrothermal synthesis of an electrochemically active NiCoMn mixed oxide (NCMO) electrocatalyst with multiple sites, porous structure, large surface area, and nanoneedle (NN) morphology deposited directly over Ni foam (NF). Sustainable electrocatalytic performance was demonstrated for 120 h in 0.2 M alkaline glycerol using chronoamperometry and chronopotentiometry. Highly selective formate production demonstrated an exclusive C-C cleavage with the present catalyst system. Oxides of individual metal-ions (Ni, Co, and Mn) and their bimetallic combination (NiCo, NiMn, and CoMn) exhibited lower activity and product selectivity than the trimetallic NCMO electrocatalyst. The membrane-free two-electrode electrolyzer setup with NCMO/NF at both the anode and cathode (NCMO/NF & Vert;NCMO/NF) requires 1.63 V to accomplish 100 mA cm-2 with 0.2 M glycerol, which is 296 mV less than that of 1 M KOH solution. High faradaic efficiency was observed for hydrogen (98%) with highly selective formate (90%) production. Electrocatalytic formate generation from an alkaline glycerol solution with NCMO is an energy-efficient and promising approach that also supplies carbon-negative green H2. NiCoMn oxide nanoneedles with a cactus-like morphology are shown as bifunctional electrocatalysts that selectively oxidize glycerol to HCOOH and concurrently produce H2.

Electrocatalytic glycerol conversion: a low-voltage pathway to efficient carbon-negative green hydrogen and value-added chemical production - Chauhan, Inderjeet; Bajpai, Himanshu; Ray, Bishakha; Kolekar, Sadhu K.; Datar, Suwarna; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Applied Materials and Interfaces, 2024)
Electrochemical glycerol oxidation reaction (GLYOR) could be a promising way to use the abundantly available glycerol for production of value-added chemicals and fuels. Completely avoiding the oxygen evolution reaction (OER) with GLYOR is an evolving strategy to reduce the overall cell potential and generate value-added chemicals and fuels on both the anode and cathode. We demonstrate the morphology-controlled palladium nanocrystals, afforded by colloidal chemistry, and their established morphology-dependent GLYOR performance. Although it is known that controlling the morphology of an electrocatalyst can modulate the activity and selectivity of the products, still it is a relatively underexplored area for many reactions, including GLYOR. Among nanocube (Pd-NC), truncated octahedron (Pd-TO), spherical and polycrystalline (Pd-PC) morphologies, the Pd-NC electrocatalyst deposited on a Ni foam exhibits the highest glycerol conversion (85%) along with 42% glyceric acid selectivity at a low applied potential of 0.6 V (vs reversible hydrogen electrode (RHE)) in 0.1 M glycerol and 1 M KOH at ambient temperature. Owing to the much favorable thermodynamics of GLYOR on the Pd-NC surface, the assembled electrolyzer requires an electricity input of only similar to 3.7 kWh/m(3) of H-2 at a current density of 100 mA/cm(2), in contrast to the requirement of >= 5 kWh/m(3) of H-2 with an alkaline/PEM electrolyzer. Sustainability has been successfully demonstrated at 10 and 50 mA/cm(2) and up to 120 h with GLYOR in water and simulated seawater.
Keywords: electrocatalysis; Glycerol; green hydrogen; nanocube; Palladium; SDG

Oxidative and selective C-C cleavage of glycerol to glycolaldehyde with atom-like Cu on Cu-TiO2: photocatalytic water reduction with concurrent glycerol oxidation in sunlight - Bajpai, Himanshu; Nivedhitha, Thazhath R.; Dais, Elsa; Kanungo, Subhashree S.; Gopinath, Chinnakonda S. (Journal of Catalysis, 2024)
Concurrent consumption of electrons and holes for the conversion of a biomass component to value added products represents a highly efficient and sustainable approach towards utilizing renewable energy, but difficult to achieve. The integration of hydrogen production with glycerol oxidation presents a novel and sustainable approach towards achieving a circular economy. In the current study, integration of atom-like Cu-clusters onto TiO2 substrate has been achieved using a facile photo-deposition technique (TC-PDO). Also, novel synthetic approaches have been employed to augment the surface coverage of Cu on TiO2 with atom-like clusters of Cu, either by borohydride treatment on TiO2 followed by Cu-deposition (TC-200) or oxygen-vacancy creation by UV illumination followed by Cu-deposition (TC-PDO). Increased dispersion and enhanced electronic integration of Cu with TiO2 lead to a corresponding increase in the efficiency of photocatalytic hydrogen evolution (13.8 mmol/h.g for TC-PDO at pH 9). Several atom-like Cu integrated with each TiO2 particle acts as photocatalytic reactor, and the same enhances electron-hole separation as well as activity. Sustainable aspect was also studied for TC-PDO up to 25 h at pH 9. Concurrently, glycerol oxidation displays the highest selectivity to C2 product (glycolaldehyde with 70 %) with a C-C cleavage. The investigation of this process holds significant potential for the extensive and simultaneous exploitation of electrons and holes in order to achieve water splitting and glycerol oxidation towards selective value-added products formation.
Keywords: C -C Cleavage; Glycerol; nanotechnology; Photo -deposition; solar energy conversion

Utilizing nature's endowment: artificial leaf concept for methane activation to C-C coupled ethanol or ethylene - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Avani, Mangaladasan J.; Bajpai, Himanshu; Salgaonkar, Kranti N.; Javaregowda, Bharathkumar H.; Gopinath, Chinnakonda S. (Sustainable Energy & Fuels, 2025)
Methane activation (MA) to platform chemicals under ambient conditions still remains an open challenge to be fully realised. The present work shows the fabrication of CeVO4 quantum dots (CV-QDs) by a bottom-up approach; they are assembled from Ce3+ and metavanadate ions, and structurally and electronically integrated into the micro-/meso-pores of TiO2 (CV-QD-TiO2 (CVT)), demonstrating the conversion of MA to ethanol/ethylene by visible light-driven photocatalysis. CV-QDs in confined pores modify the quantum confinement effects and are characterized by physicochemical methods. The current synthetic strategy is potentially scalable and results in sub-quadrillion heterojunctions in a 1 mg CVT photoanode spread over 1 cm2. MA with CVT under one-sun conditions demonstrates similar to 100% selectivity to ethanol, yielding 4.36 mu mol h-1 cm-2, with a solar-to-fuel efficiency (STFE) of 0.56. Further, by employing a co-catalyst, significant STFE (5.08) and yield (39.5 mu mol h-1 cm-2) are achieved selectively towards ethylene. A deliberate addition of methanol increases the rate of ethanol production by 17.2 times, indicating that the methyl-methoxy interaction is the origin of C-C coupling. Weight is normalized to a gram of CV-QDs in a large area CVT photoanode to yield 109 mmol h-1 gCV-QD-1 of ethanol and 988 mmol h-1 gCV-QD-1 of ethylene. Enhanced activity and selectivity towards the C2-product is attributed to band-edge modulation and trillions of heterojunctions, which in turn facilitate charge separation and charge transfer for effective charge utilisation at redox sites.